2017
DOI: 10.1094/cchem-04-16-0115-r
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Antioxidant Activity of Extruded Nixtamalized Corn Flour and Tortillas Enriched with Sorghum Bran

Abstract: Cereal Chem. 94(2):277-283Sorghum bran (SB) is a good source of phenolic compounds with high antioxidant capacity that increases the antioxidant activity (AOX) of tortillas prepared with extruded nixtamalized corn flour. The objective of this research was to study the effects of bran addition (0, 5, or 10%) before (ENBESB) or after (ENAFSB) extrusion, in the features and composition of baked tortillas in terms of total phenolic compounds (TPC), AOX, color (L, a, b, hue, chroma, and E value), and tortilla firmn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Overall, all flours presented a high proportion (46%) of fine particles <250 μm that could be related to the secondary milling, as well as the previously reported relative fragility of SB that implies its easy incorporation into cereal‐based formulations (Buitimea‐Cantúa et al., ; Chávez‐Murillo, Veyna‐Torres, Cavazos‐Tamez, de la Rosa‐Millán, & Serna‐Saldívar, ; Gomez, Waniska, & Rooney, ; Rodríguez‐Martínez et al., ) (Figure ). Other studies have related small particle size in flours with improved tortilla textural properties that are related to higher water absorption, viscosity, cohesiveness, and softness (Buitimea‐Cantúa et al., ; Gomez et al., ). Also, the processing stages for the preparation of flours play a fundamental role because it affects the particle size and increases starch damage (during grinding and regrind) and heat transfer, which affects the textural properties of tortillas (Rodríguez‐Martínez et al., ).…”
Section: Resultssupporting
confidence: 56%
“…Overall, all flours presented a high proportion (46%) of fine particles <250 μm that could be related to the secondary milling, as well as the previously reported relative fragility of SB that implies its easy incorporation into cereal‐based formulations (Buitimea‐Cantúa et al., ; Chávez‐Murillo, Veyna‐Torres, Cavazos‐Tamez, de la Rosa‐Millán, & Serna‐Saldívar, ; Gomez, Waniska, & Rooney, ; Rodríguez‐Martínez et al., ) (Figure ). Other studies have related small particle size in flours with improved tortilla textural properties that are related to higher water absorption, viscosity, cohesiveness, and softness (Buitimea‐Cantúa et al., ; Gomez et al., ). Also, the processing stages for the preparation of flours play a fundamental role because it affects the particle size and increases starch damage (during grinding and regrind) and heat transfer, which affects the textural properties of tortillas (Rodríguez‐Martínez et al., ).…”
Section: Resultssupporting
confidence: 56%
“…However, in most of the extrudates (0% sucrose) made from sorghums with low‐tannin content (BRS 373, BR 501, and CMSS 005), it was observed that the extrusion process led to considerable increases in TPC content of 71.2%, 317.5%, and 271.8%, respectively compared with raw sorghums. This phenomenon is due to the dual thermomechanical effect of extrusion process, where the high temperature caused softening of the pericarp membranes and the mechanical shearing led to the detachment and release of phenolic compounds (Buitimea‐Cantúa et al, 2017; Campelo et al, 2020) and other bioactive compounds that are bound to the insoluble fibers and trapped between the pericarp layers (Guo & Beta, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…To prepare tortillas, 3 kg of the control or experimental flours was mixed with distilled water to reach 56% moisture and further blended at low speed for 5 min in a Hobart mixer (Buitimea‐Cantúa et al, ). Resulting masas were sheeted, cut into 14‐cm‐diameter disks weighing 25 g, and continuously baked for 59 s in a three‐tier tortilla machine (Rodotec RT‐100, Tecnomaiz S.A. de C.V., Monterrey, NL, Mexico).…”
Section: Methodsmentioning
confidence: 99%